Gambaran Sistem Perawatan Kesehatan Untuk Lansia Berbasis Informasi Teknologi (Literature Review) - Komalasari, Rita (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2022)
Assisting technology for the elderly is the focus of a literature review that will help support elderly health care. This paper discusses the potential of aid technology in general to offer a cost-effective way to aid health care for the elderly; no systematic research on the cost of this technology for this population has been conducted. Throughout the evaluation process, evidence of significance was considered. This paper describes the methods and conclusions of the literature review. In conclusion of this paper, the elderly will have better access to the health care system.